The Role of Universities in Society Service in Extraordinary Unstable Conditions – Libya as a case study – - Erighib, Fatma Abdusalam (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at focusing on the role of universities in serving society and the surrounding environment during unstable (emergency) conditions, following the comparative approach with some models from western and Arab universities on one hand, and Libyan experience one the other hand, The approach of the case study is applying to Libyan universities during and after the February 17 revolution, This has a clear impact on all components of Libya society and universities, including the fact that, They are the most important and influential institutions in society in various settings at the international, regional and local levels. Also the study found that this role was generally weak, if any related to role was addressing the internal crises that universities are in between and lack of clear plans for universities Libyan universities in particular have been recommended to propose a strategy for activating the role of universities in community participation and contributing to the community participation and contributing to the community service of various institutions during unstable condition.